Effects of spatial and selective attention on basic multisensory integration - Gondan, Matthias; Blurton, Steven P.; Hughes, Flavia; Greenlee, Mark W. (Journal of experimental psychology, 2011)
When participants respond to auditory and visual stimuli, responses to audiovisual stimuli are substantially faster than to unimodal stimuli (redundant signals effect, RSE). In such tasks, the RSE is usually higher than probability summation predicts, suggestive of specific integration mechanisms underlying the RSE. We investigated the role of spatial and selective attention on the RSE in audiovisual redundant signals tasks. In Experiment 1, stimuli were presented either centrally (narrow attentional focus) or at 1 of 3 unpredictable locations (wide focus). The RSE was accurately described by a coactivation model assuming linear superposition of modality-specific activation. Effects of spatial attention were explained by a shift of the evidence criterion. In Experiment 2, stimuli were presented at 3 locations; participants had to respond either to all signals regardless of location (simple response task) or to central stimuli only (selective attention task). The RSE was consistent with task-specific coactivation models; accumulation of evidence, however, differed between the 2 tasks. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Gesehen am 07.07.2022